The Role of Aryl Hydrocarbon Receptor in Proliferation and EMT Induction in Neuroblastoma Cancer Cells (SH-SY5Y) - Mohammadi-Bardbori, Afshin; Pishavar Pour, Hesam; kargar-Abarghouei, Elias; Arab Firouzjaei, Maryam; Jamil, Maryam; Shadboorestan, Amir; Omidi, Mahmoud (Iranian Journal of Pharmaceutical Sciences, 2026)
Neuroblastoma is a common and aggressive cancer in children characterized by metastasis and uncontrolled cell proliferation. The Aryl Hydrocarbon Receptor (AhR) is a crucial regulator of diverse biological processes, such as cell growth, immune responses, and metabolism. However, its role in neuroblastoma progression is inadequately investigated. SH-SY5Y neuroblastoma cells were treated with the AhR antagonist CH223191, the agonist benzo[a]pyrene (BaP), and the endogenous ligand 6-Formylindolo[3,2-b]carbazole (FICZ). Cell viability was evaluated by MTT assay, and ROS levels were measured by dichlorofluorescein (DCF) assay, while EMT-related gene expression (vimentin and E-cadherin) was analyzed using qPCR. Compared to control, treatment with CH223191 and BaP significantly decreased cell viability and increased ROS production, respectively. BaP induced a greater reduction in viability and increase in ROS than FICZ (p < 0.01). Gene expression analysis revealed that CH223191 and BaP decreased vimentin expression (p < 0.05 and p < 0.001) and increased E-cadherin expression (p < 0.05 and p < 0.001), indicating the inhibition of EMT and promotion of epithelial characteristics. These findings highlight the pivotal role of AhR in modulating proliferation, mitochondrial function, and EMT in neuroblastoma cells, indicating that targeting AhR signaling may offer a novel therapeutic strategy to impede neuroblastoma progression and metastasis.